Virtual prototype and GaN HEMT based high frequency LLC converter design. Issue 7 (23rd April 2019) - Xiao, Long; Wu, Liang; Zhao, Jun; Chen, Guozhu
Abstract : Gallium nitride (GaN) high‐electron‐mobility transistor (HEMT) with the merits of the fast switch speed, low on resistance and low switch loss is applicable to high‐frequency LLC converters. However, voltage stress and ringing problems during the fast switching transient have retarded the promotion of switch speed and prolonged the design cycles. This study proposed an economic and time‐saving virtual prototype based LLC converter design method, based on which the voltage stress and ringing problem can be analysed and suppressed by iteration design. The virtual prototype comprises of compact GaN HEMT device model and accurate circuit model. The correctness and effectiveness of the virtual‐prototype‐based design method is verified with well matching simulation and experiment waveforms.